EDUCATIONAL VALUES IN AL-HADID'S SURAH AND ITS RELEVANCE TO CONTEMPORARY EDUCATION - Lahmuddin Lubis; Achyar Zein; Imron Bima Saputra; Rahmadi Ali (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
This study aims 1) To describe the values contained in the Quran surah Al-Hadi d, and 2) To scribe the relevance of the educational values contained in surah Al-Hadid to contemporary education. This study uses qualitative methods, and this research concerns the concept of education in the Quran. The approach used is the approach of education and interpretation through the verses of the Quran. This research focuses on surah Al-Hadi d in the Quran. The object of this study to the Quran, the approach used is the method of interpretation with tahlili, which is supported by the maudhu'i method. The results showed that: 1. Education values contained in the Quran in the Surah Al-Hadid consisting of 29 verses are as follows: 1) Praying for charity, 2) Commands of faith in Allah, 3) Prohibition of being arrogant, 4) Uphold justice, 5) Prompts for forgiveness, 6) Prohibition of miserly behavior / stingy, 7) Prompts in the form of punishment, 8) Reward in the form of rewards, 9) Nature of life in the world, 10) Trust in qadha and qadar, 11) Glorify Allah Almighty at all times, 12) Prayers of remembrance (remember Allah S.W.T.), 13) The virtue of the grace of Allah, 14) Book as a guide, 15) Prohibition of hypocrites. 2. The overall relevance illustrates the independence of education, justice, and humility in the assembly, which contains moral messages and lessons to be implemented in daily life that are sourced from the Quran, especially in today's era which is always related to increasingly complex crimeElitist education, excellent schools/madrasas.